Tafsir Ayat dan Hadist tentang Manajemen Pendidik dan Peserta Didik: Penelitian - Meli Sesmira; Risman Bustamam; Miftahul Marsena (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study discusses the interpretation of Qur’anic verses related to the management of educators and learners in Islamic education. The focus of the study includes the role of Allah as the primary educator, Prophet Muhammad as a teacher and guide for the community, teachers as facilitators of learning, parents-especially fathers and mothers- as the first educators within the family, and the importance of self-learning and self- education. The interpretation of these verses provides a strong theological and pedagogical foundation for developing an effective and sustainable Islamic education management model. This study also integrates the views of Islamic education experts who emphasize the crucial roles of educators and learners in creating a holistic educational process oriented towards character building and noble morals. Therefore, this research aims to provide a deep understanding of the concept of Islamic education management based on the Qur’an and its implications for contemporary educational practice.